2013
DOI: 10.1155/2013/297378
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and Trend of Substance Abuse in Eastern Rural Iran: A Household Survey in a Rural Community

Abstract: BackgroundA significant number of opioid-dependent patients in Iran are now being treated by methadone maintenance therapy (MMT). One of the social complications of substance dependency is family disorganization and a decrease in marital satisfaction. This study aimed to determine the effect of group therapy based on the transtheoretical model of change on family functioning of the patients under MMT.MethodsIn this open clinical trial, 48 married people who were between the ages of 19 and 40, and under methado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
1
22
2
Order By: Relevance
“…In another study conducted in 2003 in Babol province in Iran, out of 310 adults aged 16-80 years, the prevalence of opium use was 8.9% (n=42)(21) which determined that opium was the most commonly used drugs. According to a report in rural areas of Kerman province in south-east of Iran, substance use has been increased dramatically during a 12-years period (from 2000 to 2012) (22). In reports from Kerman, Golestan, Babol (Mazandaran) and Valashahr (Fars), in accordance with our study results, substance abuse, especially opium, was higher among men than women (19,21,22).…”
Section: Discussionsupporting
confidence: 90%
“…In another study conducted in 2003 in Babol province in Iran, out of 310 adults aged 16-80 years, the prevalence of opium use was 8.9% (n=42)(21) which determined that opium was the most commonly used drugs. According to a report in rural areas of Kerman province in south-east of Iran, substance use has been increased dramatically during a 12-years period (from 2000 to 2012) (22). In reports from Kerman, Golestan, Babol (Mazandaran) and Valashahr (Fars), in accordance with our study results, substance abuse, especially opium, was higher among men than women (19,21,22).…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, a population-based cross-sectional study on Iranian adolescents indicated that 15% of participants had experienced alcohol use, which is slightly higher compared to the current study findings (Ziaaddini, Ziaaddini, & Nakhaee, 2013). A previous study showed a diverging relationship between SES and alcohol use depending on the country under investigation (Room, Sujatha Sankaran, Schmidt, & Rehm, 2015).…”
Section: Discussioncontrasting
confidence: 86%
“…This was one the highest estimates in the review. As per past 30 day estimates, the Eastern Mediterranean Region, reported the highest prevalence of ever use, ranging from 15.8% in Aleppo (Syria), in 2004, to 65.3% among university students in Lebanon[ 27 – 29 , 77 , 78 , 81 ]. Studies from the Region of the Americas and Europe reported much lower prevalence estimates: 11 studies from the US ranged from 1.9% to 21.8%[ 17 20 , 79 , 80 , 83 87 ], while in Europe, ever use was reported as 11.6% among adults in the UK in 2012[ 82 ], and 19.1% among adults in a subnational household survey in Israel in 2012[ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…One US study reported particularly high prevalence, among university students, at 7.8%[ 30 ]. Other countries had higher prevalence estimates than the US: past 30 day use was reported as 2.7% in a subnational household survey among women in India in 2014[ 24 ], 6.3% among women and 11.0% among both sexes in two city-wide household surveys in Iran conducted in 2010[ 25 ] and 2012[ 27 ] respectively, 8.7% among pregnant women in maternity clinics in Jordan in 2011[ 28 ], 9.9% among university students in a subnational survey in South Africa in 2013[ 26 ], and 32.3% among university students in Lebanon in 2005[ 29 ].…”
Section: Resultsmentioning
confidence: 99%